EDUCATION FOR SUSTAINABLE DEVELOPMENT: AN EVALUATION OF THE NEW CURRICULUM OF THE FORMAL PRIMARY EDUCATION IN BANGLADESH - Fahmida Haque (European Scientific Journal, ESJ, 2014)
The social purposes of education are long term and oriented towards the construction and maintenance of a sustainable future. Primary education must receive a special attention in developing nations because it plays a vital role in fostering basic intellectual abilities such as literacy that are crucial to success. In Bangladesh the newly introduced curriculum of the primary education is a step ahead to achieve the vision of education for sustainable development. Thus the paper tries to find out what are the prospects of the new curriculum of primary education in Bangladesh as Education for Sustainable Development (ESD) and its relative problems as well. The paper also tries to find out what necessary measures to be taken to make an effective ESD curriculum for primary education in Bangladesh